Proper orthogonal decomposition analysis of near-field coherent structures associated with V-notched nozzle jets - Lim, H.D. (2021)
Time-resolved particle image velocimetry measurements and proper orthogonal decomposition (POD) analysis were conducted on freely-exhausting V-notched nozzle jets at Re = 5000. Energy redistributions from low order modes to higher order modes are observed, particularly for the first two POD modes typically associated with large-scale coherent flow structures. Furthermore, analysis of the first two POD modes reveals highly cyclical large-scale coherent flow structures formed along the nozzle peak-to-peak (PP) planes, while non-cyclical incoherent flow structures are observed along the trough-to-trough (TT) planes. POD mode coefficients reveal mode pairing behaviour along the PP-planes and reduced peak frequencies in their power spectral densities. In contrast, no mode pairing behaviour is observed along the TT-planes and multiple instances of the same frequency peak transcending two adjacent POD modes are observed instead. This suggests an energy cascade process whereby large-scale flow structures are broken down into smaller-scale ones at a common frequency. Finally, a comparatively sharper nozzle leads to earlier formations of flow structures along both PP- and TT-planes but does not significantly impact upon the periodicity or coherence of the flow structures.